Lessons learned: the role of the European Convention on Human Rights Cases of human trafficking and forced prostitution for Thailand - Noosiang, Johnson (Thai Social Science Journal, 2025)
Enforcing laws to address human trafficking and forced prostitution, which draws lessons from the legal interpretation of the European Court of Human Rights that are interpreted under the law to fall under the protection of the European Convention on Human Rights even if not expressly and directly provided for. Courts make it possible to use the law as a living tool to help combat human trafficking and forced prostitution. Courts begin to develop criteria for It and brings victims of human trafficking and forced prostitution under the protection of the Convention and goes a step further in considering victims of forced prostitution to be covered by the Convention, without considering whether it is human trafficking or not. As a result, all forms of non-consensual prostitution fall under the purview of law enforcement and no form of tacit consent is ever acceptable anymore. The court has developed a proactive procedural role for human trafficking and forced prostitution through its interpretation of the law.